Gambaran Penyebab Kematian Neonatal Di Rumah Sakit Umum Daerah Dr. M. Haulussy Ambon Tahun 2019. - Magdalena Paunno; Nenny Parinussa (MOLUCCAS HEALTH JOURNAL, 2019)
Â Neonatal mortality rates in Indonesia in 2010 were still high at 228 / 100,000 live births. Neonatal deaths can occur due to infection, asphyxia or low birth weight. While the medical records of RSUD Dr. M Haulussy Ambon is a referral center Hospital that has PONEK services that the number of neonatal deaths in 2013 was 49 cases out of 2633 live births, in 2014 there were 80 cases of 2483 KH while in 2015 in 6 months (January-July) already as many as 51 of 983 births. From the death data obtained in 2015 the causes of neonatal death are: LBW 16; Asphyxia 15; Sepsis / Infection 14; Respiratory Disorders 4; and atresia ani 2. The purpose of this study was to determine the frequency distribution of neonatal deaths and a description of the causes of neonatal death in Dr. M Haulussy Ambon in 2015. The research method is descriptive. The study population was all neonates who died in Dr. M Haulussy Ambon in 2015 recorded a diagnosis of obstetric gynecology specialist in the medical record with a total of 51 neonatal. namely data on the description of birth attendants, referral system, and maternal age less than 20 years with Neonatal death in Dr. M. Haulussy Ambon 2015. The study population was all neonates who died in Dr. M. Haulussy Ambon 2015 starting from January to July 2015 recorded in the medical record with a total of 51 neonates. The sampling technique used is total sampling. The sample in this study must meet the following criteria: neonatal and died at the age of 0-28 days and a diagnosis was given from the doctor who was on duty at the time of death. Research Instrument The instrument in this study used a checklist, which records the condition of patients who experienced neonatal death in the documentation data, namely medical records. Data The results of further research data are processed in a univariate manner, carried out by tabulating data which is then arranged in a table. The results showed that neonatal mortality of childbirth assistants by 39 health workers (76.47%) neonatal consisted of: midwives 29 (56.9%); obstetric gynecology specialist 10 (19.6%); dukun 12 (23.52%); while due to referral 15 (29.41 %%), and mortality due to maternal age 20 years neonatal mortality 5 (9.8%)